2015
DOI: 10.1017/jlg.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

On the utility of combining production data and perceptual data to investigate regional linguistic variation: The case of Spanish experiential gustar ‘to like, to please’ on Twitter and in an online survey

Abstract: The use of both production and perceptual data has the potential to provide a more complete picture of linguistic phenomena than would otherwise be the case, including when exploring regional linguistic variation. Utilizing the social networking platform Twitter and an online survey, this paper reports on a descriptive analysis of the geographic distribution of a less-commonly used syntactic form of the Spanish verbgustar‘to like, to please’, referred to as experientialgustar(e.g.,cuando gustes‘when you’d like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Twitter distributions of these features, moreover, pattern so well with traditionally observed distributions that they are eminently suited for probing regional patterns that would otherwise be too laborious to investigate. For example, Jones (2015) demonstrated that orthographically represented features of AAVE on Twitter pattern with the geographic spread of the Black population in the United States, Brown (2016) investigated the distribution of a Spanish construction on a much wider geographic scale than before, and Haddican and Johnson (2012) found that respondents from the UK and Ireland favored discontinuous particle verb orders ( she cut the melon open ), while US and Canadian participants preferred the continuous order.…”
Section: Linguistics On Twittermentioning
confidence: 99%
“…Twitter distributions of these features, moreover, pattern so well with traditionally observed distributions that they are eminently suited for probing regional patterns that would otherwise be too laborious to investigate. For example, Jones (2015) demonstrated that orthographically represented features of AAVE on Twitter pattern with the geographic spread of the Black population in the United States, Brown (2016) investigated the distribution of a Spanish construction on a much wider geographic scale than before, and Haddican and Johnson (2012) found that respondents from the UK and Ireland favored discontinuous particle verb orders ( she cut the melon open ), while US and Canadian participants preferred the continuous order.…”
Section: Linguistics On Twittermentioning
confidence: 99%
“…2 This corpus was created from online sources between 2013 and 2014, 60% of which are blogs. It should be noted before moving on that while corpora are an invaluable source of linguistic data, they are not without their drawbacks (Brown 2015). There are always issues with typographic, compilation, and tagging errors in corpora.…”
Section: Corpus Study Of Interrogative Adverbial Expressionsmentioning
confidence: 99%
“…Además, como ya señalaron estudios anteriores para el español rioplatense (Brown 2016; Elizaincín y González 2016; Elizaincín 2012), hemos visto que el uso preposicional con pronombre personal tónico [NOM + gustar + de + pronombre personal] puede expresar la atracción amorosa. Por otro lado, el empleo del sentido afectivo está mucho más extendido de lo que se ha propuesto en esos estudios previos (Brown 2016;Elizaincín y González 2016). Concretamente, se documenta en todos los países hispanohablantes, salvo en Bolivia, Costa Rica, Cuba y Puerto Rico.…”
Section: Consideraciones Finalesunclassified